IMPLEMENTING RESTORATIVE JUSTICE IN JUVENILE NARCOTICS CASES IN INDONESIA: ROLES, CHALLENGES, AND OPPORTUNITIES - Rubianti, Ni Kadek Sri Novi Wirani; Gorda, A.A.A. Ngurah Tini Rusmini; Nutakor, Briggs Samuel Mawunyo (Kanun Jurnal Ilmu Hukum, 2025)
This study analyzes the implementation of restorative justice in juvenile criminal cases involving narcotics and psychotropic substances in Indonesia, focusing on the roles of law enforcement officers, families, and communities. Employing a normative legal research method, the study utilizes statutory, conceptual, and case approaches. The findings indicate that the application of restorative justice in such cases offers a recovery-oriented solution rather than punishment, as regulated by the Juvenile Criminal Justice System Law (UU SPPA) and the Narcotics Law. Through diversion mechanisms, juveniles involved in narcotics abuse can undergo rehabilitation without undergoing a criminal justice process that could adversely affect their future. This process involves collaboration among law enforcement officers, families, and communities, where law enforcement facilitates rehabilitation, families provide emotional support and guidance, and communities work to eliminate stigma, enabling juveniles to return to school or normal activities. However, challenges remain, including limited rehabilitation facilities, a lack of understanding among law enforcement officers regarding restorative justice principles, and persistent social stigma against juveniles involved in narcotics cases. Therefore, enhancing the capacity of law enforcement personnel and developing child-friendly rehabilitation facilities are essential steps to ensure the effective implementation of restorative justice within the juvenile criminal justice system.